Pathogenesis of Diffuse Alveolar Hemorrhage in Murine Lupus. Issue 6 (5th May 2017) - Zhuang, Haoyang; Han, Shuhong; Lee, Pui Y.; Khaybullin, Ravil; Shumyak, Stepan; Lu, Li; Chatha, Amina; Afaneh, Anan; Zhang, Yuan; Xie, Chao; Nacionales, Dina; Moldawer, Lyle; et al.
Abstract : Objective: Diffuse alveolar hemorrhage (DAH) in lupus patients confers >50% mortality, and the cause is unknown. We undertook this study to examine the pathogenesis of DAH in C57BL/6 mice with pristane‐induced lupus, a model of human lupus‐associated DAH. Methods: Clinical/pathologic and immunologic manifestations of DAH in pristane‐induced lupus were compared with those of DAH in humans. Tissue distribution of pristane was examined by mass spectrometry. Cell types responsible for disease were determined by in vivo depletion using clodronate liposomes and antineutrophil monoclonal antibodies (anti–Ly‐6G). The effect of complement depletion with cobra venom factor (CVF) was examined. Results: After intraperitoneal injection, pristane migrated to the lung, causing cell death, small vessel vasculitis, and alveolar hemorrhage similar to that seen in DAH in humans. B cell–deficient mice were resistant to induction of DAH, but susceptibility was restored by infusing IgM. C3 −/− and CD18 −/− mice were also resistant, and DAH was prevented in wild‐type mice by CVF. Induction of DAH was independent of Toll‐like receptors, inflammasomes, and inducible nitric oxide. Mortality was increased in interleukin‐10 (IL‐10)–deficient mice, and pristane treatment decreased IL‐10 receptor expression in monocytes and STAT‐3 phosphorylation in lung macrophages. In vivo neutrophil depletion was not protective, while treatment with clodronate liposomes prevented DAH, which suggests that macrophage activation is central to DAH pathogenesis. Conclusion: The pathogenesis of DAH involves opsonization of dead cells by natural IgM and complement followed by complement receptor–mediated lung inflammation. The disease is macrophage dependent, and IL‐10 is protective. Complement inhibition and/or macrophage‐targeted therapies may reduce mortality in lupus‐associated DAH.